An experimental study of numerical and behavioural responses of spring staging dabbling ducks to human pedestrian disturbance - Bregnballe, Thomas; Speich, Charlotte; Horsten, Anders; Fox, Anthony D (Wildfowl, 2009)
Controlled disturbance experiments were used to study distributional and behavioural responses of spring staging dabbling ducks to pedestrians in two parts of a restored wetland (Skjern River delta, Denmark), to inform management of human access to the site. Effects of a single pedestrian on the distribution and behaviour of dabbling ducks were recorded within uniform habitat along a public path. Dabbling ducks left areas <150 m from the source of disturbance, some were displaced 150–250 m, but most birds landed >250 m away and did not return within 1 h of the disturbance. Teal Anas crecca foraging activity was significantly reduced for at least 1 h following disturbance. Wigeon A. penelope flushed when up to 250 m from the pedestrian but gradually returned to within 150–250 m of the path, with postdisturbance numbers reaching 93% of pre-disturbance numbers 1 h after the disturbance. Wigeon foraged exclusively on land, but escaped into shallow waters when the pedestrian passed. They returned to land in the same area and had resumed foraging in all zones within 15 min after disturbance. Teal abandoned a smaller study site (2.3 ha) entirely following disturbance, dispersing elsewhere in the delta, without returning for at least 1 h.